The unperfect perfectness, or remarks to reflections in connection with the Law Enforcement Lexicon (Academic Journal of Internal Affairs, 2021)
As one of the peer reviewers of the Law Enforcement Lexicon I state with full professional conviction that publication of this lexicon created a work of genre-historical importance for our law enforcement science reaching its teenage years. I would also like to record at the beginning of my reflection that I want neither praise nor blame this gigantic publication. In my notice I intend to stay impartial, objective and neutral even though I expressed my definitive recognition in the introducing sentence. This recognition means, according to my intention, rather thanks. So, I have to thank for the authors and editors as they gave a present to active contributors of law enforcement science, for people interested in it and for a wider reader public by this work appropriate to the present level of our law enforcement culture.
Keywords: law enforcement science; specialist lexicon; reflection